1,1,3-Trioxo-2H,4H-Thieno[3,4-e][1,2,4]Thiadiazine (TTD) Derivatives: a New Class of Nonnucleoside Human Immunodeficiency Virus Type 1 (HIV-1) Reverse Transcriptase Inhibitors with Anti-HIV-1 Activity - Witvrouw, M. (American Society for Microbiology (ASM), 1998)
We report the development of a new group of nonnucleoside reverse transcriptase inhibitors (NNRTIs). One of the most active congeners of this series of 1,1,3-trioxo-2H,4H-thieno[3,4-e][1,2,4]thiadiazine (TTD) derivatives, i.e., 2-(3-fluorobenzyl)-4-cyanomethylen-1,1,3-trioxo-2H,4H-thieno[3,4-e][1,2,4]thiadiazine) (QM96639) was found to inhibit human immunodeficiency virus (HIV) type 1 [HIV-1 (III(B))] replication in MT-4 cells at a concentration of 0.09 μM. This compound was toxic for the host cells only at a 1,400-fold higher concentration. The TTD derivatives proved effective against a variety of HIV-1 strains, including those that are resistant to 3′-azido-3′-deoxythymidine (AZT), but not against HIV-2 (ROD) or simian immunodeficiency virus (SIV/MAC251). HIV-1 strains containing the L100I, K103N, V106A, E138K, Y181C, or Y188H mutations in their reverse transcriptase (RT) displayed reduced sensitivity to the compounds. Their cross-resistance patterns correlated with that of nevirapine. 2-Benzyl-4-cyanomethylen-1,1,3-trioxo-2H,4H-thieno[3,4-e][1,2,4]thiadiazine (QM96521) enhanced the anti-HIV-1 activity of AZT and didanosine in a subsynergistic manner. HIV-1-resistant virus containing the V179D mutation in the RT was selected after approximately six passages of HIV-1 (III(B)) in CEM cells in the presence of different concentrations of QM96521. From structure-activity relationship analysis of a wide variety of TTD derivatives, a number of restrictions appeared as to the chemical modifications that were compatible with anti-HIV activity. Modelling studies suggest that in contrast to most other NNRTIs, but akin to nevirapine, QM96521 does not act as a hydrogen bond donor in the RT-drug complex.